Pengaruh Akuntabilitas, Transparansi, dan Partisipasi Masyarakat Pada Efektivitas Pengelolaan Dana Desa - Putra, I Made Yoga Darma; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2019)
The effectiveness of managing village funds is necessary to be able to run the village government well. Factors that influence the effectiveness of village fund management including accountability, transparency, and community participation. This study aims to determine the effect of accountability, transparency, and community participation on the effectiveness of village fund management in the Abiansemal District of Badung Regency. The sample of this study was 18 villages in Abiansemal Subdistrict with 72 respondents. The sample selection method used a purposive sampling method,  data was collected using a questionnaire. Data were analyzed using multiple linear regression analysis. The results of this study indicate that accountability, transparency, and community participation have a positive effect on the effectiveness of village fund management in the Abiansemal District of Badung Regency. This shows that the better the accountability, transparency, and community participation, the better the management of village funds in Abiansemal Subdistrict, Badung Regency. Keywords: Accountability, transparency, community participation, effectiveness of village fund management.